Inhibition of penicillin-binding protein 2a (PBP2a) in methicillin resistant Staphylococcus aureus (MRSA) by combination of oxacillin and a bioactive compound from Ramalinaroesleri. (January 2021) - Goel, Mayurika; Kalra, Rishu; Ponnan, Prija; Jayaweera, J.A.A.S.; Kumbukgolla, W.W.
Abstract: Lichens are known to be useful and important in ethanopharmacology since ages and still possess substantial interest in alternative medical practices around the world. The intent of this investigation was to evaluate and to understand the antibacterial potential of usnic acid which was isolated from Himalyan fruticose lichen Ramalina roesleri . Usnic acid is predicted for its pharmaceutical properties through in -silico studies. Binding efficiency of usnic acid with Penicillin binding protein-PBP2a, a protein which is responsible for conferring resistance in Staphylococcus aureus was accessed using in-silico interaction assays comparing with oxacillin and ceftaroline. Further, the validation of in-silico modelling was checked by determining the antibacterial potential of usnic acid against methicillin-resistant Staphylococcus aureus (MRSA) clinical isolates. In total, 28 clinical isolates collected from hospitals/medical students were included in the study and the anti-Staphylococcal activity was determined using agar plate dilution method followed by time-kill kinetics and synergistic studies. The scanning electron microscopic (SEM) pictures were obtained to show the cell wall disruption of MRSA by usnic acid. Docking results clearly indicated the enhanced binding potential of usnic acid (Glide XP G Score: 10.968; Glide energy −64.869) with PBP2a which is better than the energy range of reference compound, oxacillin (Glide XP G Score: 6.596; Glide energy −53.285) and roughly comparable to the co-crystallized ligand ceftaroline (Glide XP G Score: 12.20; Glide energy −70.322). Cefteroline is known to be more active against MRSA compared to oxacillin. The minimum inhibitory concentrations (MICs) of usnic acid against the clinical isolates of MRSA and reference strain (NCTC-6571) were in the range of 32–128 μg/ml. The high affinity of usnic acid to bind with PBP2a which is demonstrated via in-silico studies is further confirmed by the impressive inhibitory activity of usnic acid on MRSA clinical isolates. Highlights: In-silico study highlights remarkable docking properties and high affinity binding with PBP2a. Anti -MRSA activity of usnic acid was accessed using in vitro activity against 28 clinical isolates of S. aureus . Pharmacokinetic properties shows good drug likeness and follow the Lipinski's rule of 5. MICs of Usnic acid against the clinical isolates of MRSA were in the range of 32–128 μg/ml.